Cytotoxic Effects of Plant Growth Extracts Temu Giring (Curcuma Heyneana) and Temu Ireng (Curcuma Aeruginosa) against Several Cancer Cells - Sri Atun; Nurfina Aznam; Retno Arianingrum; Sri Nurestri (Jurnal Penelitian Saintek, 2010)
The purpose  of this study is to investigate  the cytotoxic  activity of extracts and fractions of the rhizoma from  temu giring and temu ireng against some cancer cells, such as breast carcinoma cells (MCF-7) and cervical carcinoma  (Ca Ski). The research method is to do with  experiments   in  the  laboratory   which   includes   extraction   and fractionation    of compounds  from   the  rhizome  from   temu  giring  and  temu  ireng,  test  the  cytotoxicity against  cancer  cells Breast  carcinoma  (MCF-7)  and cervical  carcinoma  (Ca Ski). Test results  on the activity  of extracts  and fractions  from  tubers from  temu giring  and temu ireng on breast carcinoma  (MCF-7);  Cervical carcinoma  (Ca Ski) showed good activity (below 100 µg/ml), except the methanol  extract temu ireng which shows the IC50  upper of 100 µg/ml. This indicates  that the extracts from  temu giring  and temu ireng great potential for  development  as anticancer drug.Keywoods:  Curcuma heyneana;  Curcuma aeroginosa; cytotoxic effect; anticancer